Osteoarthritis and pain [Osteoartritte aǧri nedenleri] - (:unkn) unknown (My University, 2007)
Osteoarthritis (OA) is one of the most common health problems in the aging world. Pain and stiffness are the most prominent symptoms. Despite there are numerous risk factors that to be considered as responsible, the exact pathophysiology remains uncertain. According to this enigma, there isn't any single mechanism that explains emerge of pain in OA. Pain experienced in osteoarthritic joint may not always be caused by local pathology; there are also neurologic, neuromuscular and psychosocial influences. Understanding more about the pain mechanism might help us to develop better treatment options.
Keywords: Etiology; Osteoarthritis; Pain; Pathophysiology